(untitled) (World Bulletin of Public Health, 2022)
Background Thyroidectomy aims to completely or partially remove the thyroid gland, which is located in the anterior neck area, in cases of several diseases of the thyroid gland. Objective This study aims to determine the type of complications generated as a result of thyroidectomy in Iraq. Material and method A retrospective study was conducted in Iraq on 70 patients who underwent thyroidectomy during the period from November 2020 to September 2021 at different hospitals in Iraq, and demographic data were analysed according to IBM SOFT SPSS 22. The clinical records of the patients were accessed, from which patient data were extracted in terms of gender, age, and development of the patients who underwent surgery in the mentioned period Results the complication which found in this study for 70 patient was (Hypocalcemia for nine patients with 12.6, Wound hematoma for six patients with 8.6%, External branch of superior laryngeal nerve palsy for four patients with 5.7% Conclusion A positive statistically significant relationship was found between the frequencies of type of thyroid surgery complications with a 0.056 p-value